The Effects of Geophagy on Pregnant women in Nigeria - Agene, I.J; Lar, U.A; Mohammed, S.O; Gajere, E.N; Dang, B.; Jeb, D.N; Ogunmola, J.K (American Journal of Human Ecology, 2014)
<!–[if gte mso 9]> <![endif]–> Geophagy, the act of deliberately eating clay is a common practice among pregnant women and children in Nigeria. Several edible Clays such as Montmorillonite, Chabazite-Na, Diaspore, Faujasite-Na, Lizardite-1M, Montmorillonite 15A, lizardite and Montmorillonite were collected across the country from the following states Bauchi, Benue, Gombe, Kogi, Nasarawa, Osun and Plateau respectively. Geochemical analysis were carried out using the XRD and ICP-OES to determine the elements in the clay and the mineralogy of the clay. Heavy metals analyzed for include Aluminium (AL), Arsenic (As), Chromiun (Cr), Cupper (Cu), Iron (Fe), Lead (Pb), Selinium (Se) and Zinc (Zn). The result of the analysis indicates that the Heavy metals have very high concentrations in almost all the clay samples collected. The level of contamination of As, Pb, and Se in the clays from all the states of the study area is also exceptionally high. These metals occur in concentrations far above the WHO recommended dose for human consumption and hence may contribute to so many health hazards, like deformed babies and different types of cancers among women. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>